Analisis Faktor-Faktor Motivasi Kerja Terhadap Kinerja Pegawai (Studi pada Dinas Perhubungan Kota Banjar) - Ani Widiawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study aims to determine and analyze the influence of work motivation factors consisting of compensation, promotion and work environment on employee performance at the Banjar City Transportation Agency. The formulation of the problem posed in this study is as follows: 1. How does compensation affect employee performance? 2. How does promotion affect employee performance? 3. How does the work environment affect employee performance? 4. How does the effect of compensation, promotion and work environment simultaneously on the performance of employees at the Banjar City Transportation Service? The method used in this study uses quantitative methods. Data collection techniques through questionnaires, literature, and documentation. With a research sample of 56 employees and data analysis used through statistical tests of correlation and multiple regression using SPSS version 26.00 for windows. The research results show: 1). Compensation tends to be good and employee performance is high, so that compensation has a positive and significant effect on employee performance. This means that the better the compensation, the better the performance of employees at the Banjar City Transportation Service. 2). Promotion tends to be good and employee performance is high, so promotion has a positive and significant effect on employee performance. This means that the better the promotion, the better the performance of employees at the Banjar City Transportation Service. 3). The work environment tends to be good and employee performance is high, so that the work environment has a positive and significant effect on employee performance. This means that the better the work environment, the better the performance of employees at the Banjar City Transportation Service 4). Compensation, promotion and work environment tend to be good and employee performance is high, so compensation, promotion and work environment have a positive and significant effect on employee performance. This means that the better the compensation, promotion and work environment, the better the performance of employees at the Banjar City Transportation Service Keywords: Compensation, Promotion, Work Environment, Employee Performance